Characterization of Probiotic Abilities of Lactobacilli Isolated from Iranian Koozeh Traditional Cheese - Tavakoli Mahmoud; Hamidi-Esfahani Zohreh; Hejazi Mohammad Amin; Azizi Mohammad Hossein; Abbasi Soleiman (Polish Journal of Food and Nutrition Sciences)
Eight lactic isolates including Lactobacillus plantarum (MT.ZH193, MT.ZH293, MT.ZH393 and MT.ZH593), L. casei (MT.ZH493), L. pentosus (MT.ZH693), and L. fermentum (MT.ZH893 and MT.ZH993) were identified from an Iranian traditional cheese “Koozeh Paneer” using the morphological, phenotypical, biochemical and molecular characterization and then their probiotic characteristics were compared. Results showed that the lactic isolates of L. plantarum (MT.ZH293) and L. fermentum (MT.ZH893 and MT.ZH993) were resistant to all the used bile salts up to concentrations of 0.3 to 2.0%. All the strains showed low sensitivity to the presence of conjugated bile salts. L. plantarum MT.ZH293 exhibited the highest enzymatic activity of β-galactosidase and survival rate in a simulated stomach duodenum passage. L. casei MT.ZH493 generated the highest amount of hydrogen peroxide, followed by L. fermentum MT.ZH993 and L. plantarum MT.ZH593. Although the most selected LAB isolates had a moderate cell surface hydrophobicity, L. plantarum MT. ZH593 expressed the highest cell surface hydrophobicity. L. fermentum MT.ZH893 had strong resistance to all the antibiotics tested such as amoxicillin, ceftriaxon, chloramphenicol, erythromycin, gentamycin, streptomycin, tetracycline and vancomycin. Five lactic strains of L. plantarum (MT.ZH193, MT.ZH393 and MT.ZH593) and L. fermentum (MT.ZH893 and MT.ZH993) inhibited the growth of the tested foodborne pathogens including Escherichia coli PTCC5052, Salmonella enterica, Enetrococcus hirea, Staphylococcus aureus and Pseudomonas aeruginosa.